STUDI KESESUAIAN LAHAN POTENSIAL UNTUK TANAMAN KELAPA SAWIT DI KABUPATEN BLITAR - Edi Sasongko, Purnomo (MAPETA, 2010)
Palm oil is one of the superior commodities in Indonesia, so it needs to be explored further development in order to produce well through the growth of land suitability. Oil palm cultivation is scattered in 22 provinces in Indonesia have not centrally managed. The main problems of oil palm cultivation in Blitar caused by the still limited extent of the planting area and the low productivity and quality of palm oil, institutional, farm and business partnerships were not functioning effectively. Another factor is the suitability of land, climate, varieties and use of genetic degradation, the use of fertilizers, pesticides and weaknesses of harvest and post harvest handling.Keyword : planting areas, palm oil, land suitability, production, degradation